The effect of mixed convection on particle laden flow analysis in a cavity using a Lattice Boltzmann method - Che Sidik, Nor Azwadi (Elsevier, 2014)
In this paper a point-force scheme was developed to simulate a particle laden flow under the effects of mixed convection while the hydrodynamic removal of contaminants contained in a cavity was studied. The process of fluid renewal in a cavity was modeled using a Lattice Boltzmann method coupled with a double population scheme of energy evolution. Point-particle formulation accounts for the finite-size dispersed phase and the forces acting on the particles were modeled through drag force correlations. Two-way interaction of solid-fluid calculation was considered by adding an external force term for feedback forcing of particles in the fluid distribution function evolution. This study focused on the effects of mixed convection on the transient development of a cavity flow and the efficiency of the cleaning process. The results illustrate that the variations in the Grashof number made a remarkable difference in the observed flow pattern and cleaning efficiency.